MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V SD ZAINUDDIN PADA PEMBELAJARAN IPAS DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Fatma Hardini; Lina Listiana; Dyah Eka Sulistyorini (Universitas Muhammadiyah Surabaya, 2024)
This research aims to improve the motivation and learning outcomes of class V-B students at Zainuddin Elementary School through the application of the Problem Based Learningmodel to material on the human digestive system. The type of research used is quasi-experimental research. The research design is a pre-test and post test control group design. The subjects of the research carried out were 28 students in class VB of Zainuddin Elementary School, totaling 28 people for the 2023/2024 academic year. Data collection techniques were by observation and tests. The research instrument used learning implementation observation sheet, cognitive test sheets, and motivational observation sheets. The results of observation of students' attitudes showed that 86% met the KKTP, the learning outscome of students showed 93% met KKTP, the results of students' skills met 100% of the KKTP. The results of the reflection showed that 93% of students felt happy and could understand the material being taught. The conclusion of this research is that the application of the Problem Based Learning Model is effective in improving student learning outcomes.